Christian Saluan: The Existence Of The Saluan “Monika” Life Cycle Ritual In The Gklb Betania Sinampangnyo Congregation - Yohanes Bandong (Jurnal Ilmiah Sosiologi Agama (JISA), 2022)
The Saluan tribe is one of the tribes who inhabit the Banggai Regency, Central Sulawesi. The majority of this tribal community is Muslim and has a distinctive tribal language that is used in even daily rituals, namely the Saluan language. This article aims to see the existence of life cycle rituals carried out by the Saluan tribal community who are Christian. The life cycle ritual carried out by the Saluan Christian tribal community is realized through the traditional Saluan "Monika" marriage, which is held in the GKLB Betania Sinampangnyo congregation. The life cycle ritual is able to become a symbolic interaction space by making the traditional marriage of the Saluan "Monika" tribe as part of the GKLB Betania Sinampangnyo congregation. This study uses qualitative research with a descriptive approach. The results of this study indicate that, first, the existence of life cycle rituals opens up space for symbolic interactions between Christianity and Saluan culture in individuals, married couples, families and the GKLB Betania Sinampangnyo congregation. Second, the existence of life cycle rituals makes it clear that in the traditional marriage of the Saluan “Monika” tribe in the GKLB Betania Sinampangnyo congregation, Malinowski's theory of cultural functions occurs. This article will be part of a study of observations, interviews and literature in collecting data and presenting data in a qualitative-descriptive manner using a phenomenological approach as a research method supported by theoretical concept of "rites de passage" theory from van Gennep which will be used as a surgical medium to observe and explain life cycle rituals in the traditional marriage of the Saluan "Monika" in the GKLB Betania Sinampangnyo congregation.